Nutritional analysis of selected wild edible vegetables of the Vhembe region, South Africa - Mokganya, Mokgaetji Georginah; Tshisikhawe, Milingoni Peter; Mushaphi, Lindelani Fhumudzani; Amoo, Stephen; Potgieter, Martin (Technium Social Sciences Journal, 2021)
For rural communities, wild edible plants play a paramount role as foods, which improve their nutritional livelihood and combat food insecurity. The prevalence of Vitamin A, Vitamin C, Fe, and Zn from eight wild edible vegetables were studied. The micronutrients have the highest deficiency prevalence in human in the Vhembe region of the Limpopo Province, South Africa whereas trace elements studied in this research play indispensable roles in the maintenance of health and disease states of humans and domestic animals. Plant samples (leaves), free of infections, were obtained from street hawkers located between Levubu and Makhado in the province. Analysis of Fe, Zn, b-carotene and quantification of Vitamin C was achieved by following methods which are explained in the methodology section with slight modifications. Amaranthus Hybridus L. contained high amounts of 226±3.06 mg/100g and 15.5+/-3.52 mg/100g of Fe and Zn respectively. Solanum retroflexum was found to have the highest amount of Vitamin A (b-carotene) of 10.91 mg/100g DW , while Amaranthus thunbergii contained the highest (69.11mg/100g DW) amount of Vitamin C. There is a chance of blending wild edible vegetables for consumption. The blending of Solanum retroflexum and Amaranthus thunbergii is therefore recommended as it promotes Vitamin A and Vitamin C contents in the diet of humans.